2010
DOI: 10.1111/j.1365-2842.2010.02182.x
|View full text |Cite
|
Sign up to set email alerts
|

Tongue strength of healthy young adults

Abstract: The measurement of tongue strength contributes to the study of oro-facial physiology. The objective of this study was to investigate the influence of gender on tongue strength in young adults and to determine the differences in this strength between tongue regions. This study was conducted on 50 healthy volunteers (17 men and 33 women) with a mean age of 23 years, with no oro-facial myofunctional alterations. The strength of the anterior portion and of the dorsum of the tongue was analysed with a calibrated el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
14

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 24 publications
1
38
0
14
Order By: Relevance
“…Besides, it is possible to find studies related to the exercises of the tongue (17) ; pressure of the lip and tongue regarding the type of bad occlusion (19) ; the comparison between the maximum isometric pressure of the tongue of individuals with dentofacial deformity and those with adequate occlusal relationship (20) ; and the comparison of pressure and resistance of the tongue among speakers of Brazilian Portuguese, and English, which obtained a lower resistance of the tongue for the latter (13) . The diversity of instruments used to measure the pressure of the tongue and the lack of standardization in the evaluation of this skill makes it difficult to reproduce studies and to compare results (3,11,15) . Therefore, obtaining the values of pressure of the tongue in different tasks and the resistance of the tongue by the IOPI system, in a population of young adults, will help to understand the functioning of this structure and the diagnosis of oral dysfunctions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, it is possible to find studies related to the exercises of the tongue (17) ; pressure of the lip and tongue regarding the type of bad occlusion (19) ; the comparison between the maximum isometric pressure of the tongue of individuals with dentofacial deformity and those with adequate occlusal relationship (20) ; and the comparison of pressure and resistance of the tongue among speakers of Brazilian Portuguese, and English, which obtained a lower resistance of the tongue for the latter (13) . The diversity of instruments used to measure the pressure of the tongue and the lack of standardization in the evaluation of this skill makes it difficult to reproduce studies and to compare results (3,11,15) . Therefore, obtaining the values of pressure of the tongue in different tasks and the resistance of the tongue by the IOPI system, in a population of young adults, will help to understand the functioning of this structure and the diagnosis of oral dysfunctions.…”
Section: Introductionmentioning
confidence: 99%
“…It is portable and easy to use, is noninvasive, and presents fast, accurate, and reliable measurements (4)(5)(6) . After that, many studies proposed to measure the pressure made by the tongue on the oral cavity (7) during functions such as speech (8) , swallowing, (5) and chewing (9) ; at rest (10) ; and during the maximum isometric contraction for comparing with different portions of the tongue (anterior and dorsum) among young adults (11) . The pressure of the tongue has also been studied in relation to gender (11)(12)(13)(14) and age (5,(13)(14)(15) in individuals diagnosed with obstructive sleep apnea (16) , neurological conditions (17) , and disorders in the head and neck area (18) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alguns instrumentos apresentaram características específicas que não permitiram o agrupamento em nenhuma das categorias definidas [26][27][28][29][30][31][32][33] . Observa-se também instrumentos com utilização restrita em pacientes com dificuldade de deglutição, devido ao risco de aspiração de água 28 .…”
Section: Figura 4 -Dispositivos Que Empregam Outras Tecnologiasunclassified
“…Some studies found greater force in men (2,6,13,(15)(16)(17) . However, in other studies such difference was not observed (12,14,(18)(19)(20)(21)(22) .…”
Section: Introductionmentioning
confidence: 99%